Greenness and allergic rhinitis in children: the moderating and mediating effects of meteorological factors and air pollution - Hu, Yabin; Yang, Guiyan; Wang, Dan; Gu, Wangyang; Li, Qingpeng; Xu, Linling; Tang, Jingyi; Wei, Hui; Tong, Shilu; Li, Zonghua; Liu, Shijian (Frontiers in Climate, 2025)
BackgroundEmerging evidence suggests that greenness may be beneficial to human health; however, the relationship between greenness exposure and childhood allergic rhinitis (AR) is inconsistent, and whether and how the link is moderated or mediated by meteorological factors and air pollutants remains unclear.MethodsWe conducted an observational study in Sanya, China. Information on AR and covariates was collected from e-questionnaires. Greenness exposure was assessed using satellite-estimated data based on the normalized difference vegetation index (NDVI) and the enhanced vegetation index (EVI). Binomial generalized linear models with a log link were used to evaluate the associations between greenness exposure and childhood AR, presented as prevalence ratio (PR) and 95% confidence interval (CI) per interquartile range (IQR) increase in greenness, adjusting for potential confounders. Stratified analyses and mediation analyses were also performed.ResultsOf the 9,754 children included in the study, the prevalence of ever AR (EAR) and current AR (CAR) was 15.6 and 23.2%, respectively. An IQR increase in greenness was associated with an attenuated PR of childhood AR. The PRs (95% CIs) were 0.95 (0.88–1.02), 0.94 (0.88–1.00), 0.94 (0.89–0.99), and 0.95 (0.90–0.99) for EAR-NDVI, EAR-EVI, CAR-NDVI, and CAR-EVI, respectively. Furthermore, these associations existed only in boys [PRs (95% CIs) were 0.92 (0.85–0.99), 0.92 (0.85–0.98), and 0.93 (0.88–0.99) for EVI-EAR, NDVI-CAR, and EVI-CAR, respectively], and low-temperature groups [PRs (95% CIs) were 0.89 (0.80–0.99), 0.87 (0.78–0.97), 0.91 (0.84–0.98), and 0.92(0.85–0.99) for NDVI-EAR, EVI-EAR, NDVI-CAR, and EVI-CAR, respectively]. Ambient temperature and relative humidity were found to mediate these associations.ConclusionGreenness exposure seems to reduce the prevalence ratio of childhood AR. These associations may be more pronounced in boys and in low-temperature groups and were mediated by ambient temperature and relative humidity. These findings offer new perspectives for considering ambient temperature and relative humidity in relation to greenness exposure and children’s health.